Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0227766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregravid obesity on perinatal outcomes in singleton pregnancies following in vitro fertilization and the weight-loss goals to reduce the risks of poor pregnancy outcomes: A retrospective cohort study

Abstract: In the present study, we aimed to determine whether pregravid obesity independently predicts increased risks of perinatal complications following in vitro fertilization (IVF) and the weight loss goals to reduce the risk of poor pregnancy outcomes. Design Retrospective cohort study. Population All pregnancies after first the fresh IVF cycle from January 2014 to December 2016 in the Reproductive Center affiliated to Shandong University were reviewed. A total of 3,962 eligible singleton births were stratified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“… 24 A reduction in pregravid BMI for overweight and obese women was associated with a significant reduction in caesarean deliveries. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 A reduction in pregravid BMI for overweight and obese women was associated with a significant reduction in caesarean deliveries. 25 …”
Section: Discussionmentioning
confidence: 99%
“…24 A reduction in pregravid BMI for overweight and obese women was associated with a significant reduction in caesarean deliveries. 25 Obesity adversely affects the maternal milieu by increasing the risk of gestational diabetes and hypertensive disease in pregnancy. 5 A previous study reported that abnormal weight did not affect pregnancy outcomes in women with PCOS that underwent frozen embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women with pre-pregnancy obesity were more likely to give birth to infants with macrosomia. A study in China also showed that obesity was associated with an increased risk of macrosomia in ART singleton pregnancies ( 22 ). Other studies have shown increased risks of gestational hypertension, preeclampsia, gestational diabetes, and cesarean section in overweight or obese women who conceived through IVF ( 23 25 ), which is consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, maternal HDP and fetal macrosomia were more likely to occur among younger women with high BMI. Liu et al 30 also reported that obesity might raise the risk of some poor prenatal outcomes through the development of GDM and HDP. Therefore, the fetus is more likely to be exposed to an adverse intrauterine environment, resulting in an increased incidence of fetal macrosomia and cesarean delivery, which, in turn, increases the risk of childhood and adult obesity.…”
Section: Main Findings and Interpretationsmentioning
confidence: 99%
“…Kort et al 31 showed that 10% weight loss could enhance LBR in overweight/obese women. Liu et al 30 also suggested a 10%-15% reduction in pre-pregnancy maternal BMI for obese women and a 5% reduction for overweight women to lower the incidence of prenatal outcomes. Based on the above evidence, younger women with elevated BMI should consider losing weight before pregnancy, but older women do not have to delay pregnancy to achieve weight loss as they need to balance against the risk of agerelated fertility decline.…”
Section: Main Findings and Interpretationsmentioning
confidence: 99%